Mentoring of SMEs by big corporate industries as a way of mitigating the negative impact of HIV/AIDS, with particular reference to the Western Cape. - Mzizi, Thandi (Stellenbosch : University of Stellenbosch, 2006)
Thesis (MPhil (Industrial Psychology))--University of Stellenbosch, 2006.